2008
DOI: 10.2463/mrms.7.169
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Unruptured Intracranial Aneurysms: 3T MR Angiography versus 64-channel Multi-detector Row CT Angiography

Abstract: Three-tesla, 3D TOF MRA and 64-MDCTA are excellent modalities with high diagnostic accuracy for evaluating unruptured intracranial aneurysms and no significant difference between them in diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 31 publications
5
53
1
Order By: Relevance
“…According to a recent study, 3T TOF MRA demonstrated a screening sensitivity of 67% for aneurysms of Ͻ3 mm, 79% for those of 3-5 mm, and 95% for those of Ͼ5 mm. 36 Because many patients have multiple aneurysms (ϳ30%), 37 a per-patient screening sensitivity is a more accurate metric for assessing the effectiveness of a technique. In this study, the per-patient screening sensitivity and specificity were 96% and 92%, respectively.…”
Section: Efficacy and Safetymentioning
confidence: 99%
“…According to a recent study, 3T TOF MRA demonstrated a screening sensitivity of 67% for aneurysms of Ͻ3 mm, 79% for those of 3-5 mm, and 95% for those of Ͼ5 mm. 36 Because many patients have multiple aneurysms (ϳ30%), 37 a per-patient screening sensitivity is a more accurate metric for assessing the effectiveness of a technique. In this study, the per-patient screening sensitivity and specificity were 96% and 92%, respectively.…”
Section: Efficacy and Safetymentioning
confidence: 99%
“…Technical advances in magnetic resonance angiography (MRA) have increased the chances of detecting unruptured intracranial aneurysms (UIAs) [1,2], and the prophylactic treatment of UIAs is now a major focus of efforts to reduce the overall mortality and morbidity of subarachnoid hemorrhage (SAH) by UIA rupture. …”
Section: Introductionmentioning
confidence: 99%
“…Three of the included studies 16,24,25 evaluated diagnostic performance of MRA and CTA among their study population, with observers blinded to the results of other imaging examinations. In total, 263 patients with 220 aneurysms underwent both noninvasive imaging tests.…”
Section: Comparison With Ctamentioning
confidence: 99%
“…[26][27][28][29][30][31] In total, 12 articles were included in the meta-analysis. [14][15][16][17][18][19][20][21][22][23][24][25] The study characteristics are shown in Table 1. All included studies had a consecutive design and used DSA as the reference standard.…”
Section: Study Identification and Study Characteristicsmentioning
confidence: 99%